Where is the Love? Using the Black Eyed Peas to Reach Expository Writing Students - Blackburn, Heidi; Molidor, Jennifer (My University, 2011)
Over the last year, the K-State at Salina Library has created and renovated a project utilizing contemporary music as a way to connect with students and provide research topics in an Expository Writing course. In 2003, the song “Where Is the Love?” by international music sensation The Black-Eyed Peas, swept the tops of billboard charts. With a hip-hop vibe and boundary-crossing critique of war, terrorism, discrimination, and hate crimes, the song’s themes moved fans of all ages, races, and backgrounds. Using this connection, our project emphasizes cross-departmental collaboration, and is grounded in the belief that in Freshman Composition courses the writing professor and the research librarian must work together for successful writing and research based projects. In “Writing Information Literacy: Contributions to a Concept” Rolf Norgaard (2003) urges librarians and writing instructors to have “informed conversation between writing and information literacy as disciplines and fields of endeavor.” Following this approach, the results of our activity initiated a coordinated restructuring of the library-writing course curriculum. This paper will focus on student learning outcomes, challenges of the activity, student feedback, and post-assessment adjustments.
Keywords: Library Instruction; Information Literacy; Z711